2000
DOI: 10.1046/j.1439-0434.2000.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Field Application of Tebuconazole on Yield, Yield Components and the Mycotoxin Content of Fusarium-infected Wheat Grain

Abstract: Winter wheat cultivar Basalt was artificially inoculated with Fusarium culmorum at the end of anthesis and treated with the systemic fungicide tebuconazole (Folicur®) a few days before and/or after inoculation. Check plots remained uninoculated and unsprayed. Head infections, yield, yield components and the percentage of Fusarium‐ infected kernels were determined. Artificial Fusarium inoculation lowered yield significantly by 24.2‐45.0%. Any fungicide treatment saved yield, thousand grain weight and kernel num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…In other researches, many other authors stated a 22-72% reduction of the DON content, while using the prothiconazole + tebuconazole fungicide mixture (Homdork et al 2000;Hart et al 2001;McMullen et al 2001;Lechoczki-Krsjak et al 2008). The results of our trial showed an even greater decrease of the DON content.…”
Section: Don Content Fhb Incidence and Fdksupporting
confidence: 57%
See 1 more Smart Citation
“…In other researches, many other authors stated a 22-72% reduction of the DON content, while using the prothiconazole + tebuconazole fungicide mixture (Homdork et al 2000;Hart et al 2001;McMullen et al 2001;Lechoczki-Krsjak et al 2008). The results of our trial showed an even greater decrease of the DON content.…”
Section: Don Content Fhb Incidence and Fdksupporting
confidence: 57%
“…Such conditions lower the quality of wheat, which results in a lower thousand-grain weight and a higher percentage of fine, scabby and coloured grains. Various studies showed that FHB can be efficiently controlled by using the prothiconazole + tebuconazole fungicide mixture, which can reduce the DON content by 22-72% (Homdork et al 2000;Hart et al 2001;McMullen et al 2001). Miedaner (2012) stated that contamination can be reduced by 50-70%, while the DON content in grains can be lowered by 50-80%.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, pesticide application has been an important way to improve wheat yield. TEB and TBM are two commonly used pesticides in wheat field, and they play an important role in controlling diseases and weeds (Homdork et al, 2000;Mukherjee et al, 2015). Besides, the dissipation studies of TEB and TBM in wheat and soil have been widely investigated in previous couple of years.…”
Section: Introductionmentioning
confidence: 99%
“…Head infection, yield, yield components and the percentage of Fusarium-infected grains were determined in many studies connected with FHB (Homdork et al 2000). With the development of chemical methods, the assessment of plant resistance to fusa rium head blight started to be supplemented with chemical analyses, which facilitated the determination of mycotoxin concentrations in grain (Kubo et al 2014).…”
Section: Introductionmentioning
confidence: 99%